Bacterial Memory of Persisters: Bacterial Persister Cells Can Retain Their Phenotype for Days or Weeks After Withdrawal From Colony–Biofilm Culture - Miyaue, Saki; Suzuki, Erika; Komiyama, Yoko; Kondo, Yu; Morikawa, Miki; Maeda, Sumio (Frontiers in Microbiology, 2018)
Persister cells, or persisters, are a specific subpopulation of bacterial cells that have acquired temporary antibiotic-resistant phenotypes. In this study, we showed that Escherichia coli produces many more persister cells in colony–biofilm culture than in the usual liquid culture and that these persisters can be maintained in higher numbers than those from liquid culture for up to 4 weeks at 37 °C in a fresh, nutrient-rich, antibiotic-containing medium, even after complete withdrawal from the colony–biofilm culture. This suggests the presence of a long-retention effect, or “memory effect”, in the persister cell state of E. coli cells. We also discovered that such increases in persisters during colony–biofilm culture and their memory effects are common, to a greater or lesser degree, in other bacterial species. This is true not only for gram-negative bacteria (Acinetobacter and Salmonella) but also for gram-positive bacteria (Staphylococcus and Bacillus). This is the first report to suggest the presence of a common memory mechanism for the persister cell state, which is inscribed during colony–biofilm culture, in a wide variety of bacteria.